Waging war in fourth-century Athens
1 online resource (344 pages)
Keywords: This volume provides a new assessment of Athens' military capabilities and war efforts in the fourth century BC, highlighting the close connection between its democracy and military affairs.Athens after the Peloponnesian War has been the subject of intense study, particularly its military capabilities and war efforts and the workings of its democracy. We still do not have, however, a comprehensive assessment of Athens' military record in the fourth century. This book provides a new detailed picture of this period, exploring what Athens was capable of and what it achieved militarily and diplomatically after its defeat in the Peloponnesian War. The volume also reassesses aspects of Athenian warmaking and warfare, including diplomatic and economic matters, from 404 BC down to and including the Lamian War of 323-322 BC.Waging War in Fourth-Century Athens: New Appraisals is suitable for students and scholars in Classics and Ancient History, as well as those operating in adjacent fields of study, along with the general reader interested in the ancient world, warfare, and politics.